ANN and Machine Learning Techniques for Diagnosis of Thyroid Disorders - Bhausaheb Namdeo Rajole, Dr. Vitthal J. Gond (International Journal of Advanced Science and Technology, 2020)
In this paper, we understand the normal structure and function of the Thyroid gland, types of thyroid disorders, problems due to disorder of Thyroid gland and methods available in market for diagnosis of Thyroid disorders. The main aim of this paper is to review the different feature extraction techniques, machine learning algorithms, classification algorithm, optimization algorithms and different types of Artificial Neural Networks in order to eliminate false diagnosis and to improve the diagnostic accuracy in detection of thyroid disorders.